Fine needle aspiration biopsy of mandible: an effective alternative to conventional biopsy for the differential diagnosis between metastasis and osteonecrosis in oncologic patients treated with bisphosphates - Case report - Baldi, Débora Silva; Pinto, Fabiano Saggioro; Ferrari, Tatiane Cristina; Ramos, Lara Maria Alencar; Macedo, Leandro Dorigan de (Journal of Oral Diagnosis, 2017)
Bisphosphonates are the drugs of choice for the prevention and treatment of bone metastases of breast cancer, especially in more advanced cases. Osteonecrosis of the jaw (BRONJ) is the most common, debilitating complication of the use of this drug, caused mainly by bone manipulation. Because of this, the indication for biopsy for differential diagnosis is critical in cases of radiographic findings without mandibular exposure, and less invasive diagnostic methods have been discussed in the literature. The objective of this study was to describe a case of differential diagnosis of mandibular metastasis of breast cancer and BRONJ by fine needle aspiration (FNA). A 67-year-old woman was referred to the Dentistry and Stomatology Service of Ribeirao Preto General Hospital, Brazil, in January 2015, for investigation of pain followed by paresthesia in the lower lip. The patient had a history of mixed breast carcinoma in 1999, recurrent in 2010, treated with chemotherapy and Zometa from 2010 to 2013. Although no significant alterations were detected at clinical examination, the CT scan revealed osteolytic lesions involving the anterior and posterior right jaw. Because of the risk of bone necrosis after biopsy, FNA was chosen as the diagnostic method. Cytology confirmed metastasis of breast cancer and the patient had no complications in the puncture area. FNA was shown to be a viable, safe option for differential diagnosis between BRONJ and mandibular bone metastasis.